PENGUATAN DAYA SAING UMKM DI KABUPATEN BOLAANG MONGONDOW SELATAN: PENGARUH PEMBERDAYAAN, KEMUDAHAN PERIZINAN, INOVASI BISNIS, DAN DUKUNGAN PEMERINTAH - Citra Amaliah Ali; Yakup; Deby R. Karundeng (JUIMA : JURNAL ILMU MANAJEMEN, 2026)
This study analyzes the influence of empowerment, ease of licensing, business innovation, and government support on the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in South Bolaang Mongondow Regency. The research employs a quantitative explanatory design supported by qualitative data obtained through interviews and observations. Primary data were collected using a Likert 1–5 scale questionnaire from 100 MSME actors in the trade, services, culinary, and household industry sectors, selected through non-probability sampling. Multiple linear regression analysis was conducted after fulfilling validity, reliability, and classical assumption tests. The simultaneous test indicates that the four variables significantly affect MSME competitiveness (F=13.559; p<0.001), with an Adjusted R²=0.337. Partially, empowerment, ease of licensing, business innovation, and government support each have a positive and significant effect on MSME competitiveness (p<0.05), with empowerment showing the largest contribution. The findings suggest that strengthening MSME competitiveness cannot rely on a single intervention but requires an orchestrated policy approach that integrates capacity building of business actors, inclusive licensing services, sustainable innovation development, and government support grounded in a measurable market ecosystem. This study contributes theoretically by integrating internal and external factors within a single empirical framework of MSME competitiveness, while providing policy input for local governments to strengthen the sustainability of local MSMEs.